Determination of Physical Enviroment Factor Levels to Improve Productivity in the Filleting Process: Case Study: PT Bumi Menara Internusa - Chenwidy, Johan; Hadi, Yuswono; Noya, Sunday (Teknik Industri Universitas Ma Chung, 2024)
PT Bumi Menara Internusa Surabaya is a producer of processed frozen seafood products, which uses a lot of human resources in its production. The use of human resources in the production process is closely related to productivity which will ultimately affect work efficiency and effectiveness. PT Bumi Menara Internusa itself has many products from various types of fish, one of which is salmon. The production process for frozen salmon products has several processing stages, one of which is the filleting process. The filleting process is a process where the fish flesh is separated from the fish backbone. To determine employee productivity in the production of frozen salmon products, employee output will be recorded every hour. Based on observations, records held by the company and interviews that have been conducted, it was found that employees in the fillet section were often unable to achieve the daily output targets that had been planned and calculated by the department concerned. Therefore, research was carried out using the Taguchi method to increase the productivity of salmon fillet employees. The results of the research carried out were an increase in productivity value of 3.556.